Reproducibility Distinguishes Conscious from Nonconscious Neural Representations - Schurger, Aaron; Pereira, Francisco; Treisman, Anne; Cohen, Jonathan D (Science (American Association for the Advancement of Science), 2010)
What qualifies a neural representation for a role in subjective experience? Previous evidence suggests that the duration and intensity of the neural response to a sensory stimulus are factors. We introduce another attribute--the reproducibility of a pattern of neural activity across different episodes--that predicts specific and measurable differences between conscious and nonconscious neural representations indepedently of duration and intensity. We found that conscious neural activation patterns are relatively reproducible when compared with nonconscious neural activation patterns corresponding to the same perceptual content. This is not adequately explained by a difference in signal-to-noise ratio.